Pengaruh Pendidikan Kesehatan Tentang Tanda Bahaya Kehamilan Pada Ibu Hamil Dengan Resiko Tinggi - Achmad Vindo Galaresa; Priyoto Priyoto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Pregnancy is a normal and natural process in a woman where physical, psychological and social changes occur during pregnancy. Knowledge of pregnancy danger signs is important for the community, especially pregnant women with high risk, because if the danger signs are known early, the handling will be faster. The purpose of this study was to determine the difference in the level of knowledge of pregnant women with high risk about pregnancy danger signs before and after being given counseling at the Mejayan Health Center, Madiun Regency. This type of research is Quasy Experimental with the One Group Pre-Test-Post-Test approach. The respondents used were 17 with total sampling. The instrument used was a questionnaire that had been tested for validity. Data analysis used a paired t-test. The conclusion from the results of the data analysis obtained a p value = 0.000 which stated that there was a significant difference in the knowledge of pregnant women before and after being given health counseling about the dangers of pregnancy using leaflets and videos. It is hoped that these suggestions can be input for pregnant women to be more active in seeking information and for health workers to be more active in providing health counseling and facilitating pregnant women regarding pregnancy danger signs.